2020
DOI: 10.1016/j.genrep.2020.100956
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analyses of significant genes, related pathways, and candidate diagnostic biomarkers and molecular targets in SARS-CoV-2/COVID-19

Abstract: Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) infection is a leading cause of pneumonia and death. The aim of this investigation is to identify the key genes in SARS-CoV-2 infection and uncover their potential functions. We downloaded the expression profiling by high throughput sequencing of GSE152075 from the Gene Expression Omnibus database. Normalization of the data from primary SARS-CoV-2 infected samples and negative control samples in the database was conducted using R software. Then, joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 167 publications
(127 reference statements)
1
33
0
Order By: Relevance
“…A previous work reported that JNK cascade was activated in influenza A virus-infected neurons, while a delayed p38 activation was visible in astrocytes [ 66 ]. JUN and FOS were downregulated, as found also in a transcriptomic analysis of nasopharyngeal swabs of SARS-CoV-2 positive compared to negative subjects [ 67 ]. Interestingly, JUN transcript was restricted at post transcriptional level by SARS-CoV-2 [ 68 ], also due to its short half-life [ 69 ].…”
Section: Discussionmentioning
confidence: 86%
“…A previous work reported that JNK cascade was activated in influenza A virus-infected neurons, while a delayed p38 activation was visible in astrocytes [ 66 ]. JUN and FOS were downregulated, as found also in a transcriptomic analysis of nasopharyngeal swabs of SARS-CoV-2 positive compared to negative subjects [ 67 ]. Interestingly, JUN transcript was restricted at post transcriptional level by SARS-CoV-2 [ 68 ], also due to its short half-life [ 69 ].…”
Section: Discussionmentioning
confidence: 86%
“…As previous studies confirmed that IGFBP5 plays role in key positions such as inducing cell adhesion, increasing cell survival and inhibiting cell migration in MCF-7 human breast cancer cells ( Sureshbabu et al, 2012 ) and reported as one of the significant genes of COVID-19 ( Vastrad et al, 2020 ). These outcomes confirm the key task of the Interleukin-3-mediated signaling pathway engaged in breast cancer, COVID-19, and treatments of similar infectious diseases offering new molecular therapeutic targets to improve fundamental drug agents.…”
Section: Resultsmentioning
confidence: 57%
“…The proteins encoded by the CXCL9 and CXCL10 genes are highly significant players in the so-called “cytokine storm” produced by the corona-virus infection 37 . In addition, PCSK5, ROCK1P1, RPLP1, and NDUFV1 were found to be differentially expressed between SARS-CoV-2 infected patients and non-infected individuals in the study of Vastrad et al 36 . These data confirm that features selected by AutoML are biologically relevant, some of them already confirmed, others emerging here for the first time.…”
Section: Discussionmentioning
confidence: 88%
“…These findings seem highly relevant biologically and are novel, showing the potential of the AutoML method to unravel new players in the pathological process. Among the common features, IFI27 was found to be up-regulated in the COVID-19 patients compared to the controls in the study of Huang et al 35 while the FAM83A has been found to be differentially expressed between SARS-CoV-2 infected patients and virus-free individuals 36 .…”
Section: Discussionmentioning
confidence: 92%